College Alcohol Citations Result in Modest Reductions in Student Drinking - Hustad, John T.P. (2010)
College students who are cited for violating campus alcohol policy are often fined or sanctioned to complete an intervention or public service. While some interventions have been found efficacious for mandated students, it is possible that being cited for an alcohol-related incident alone may be sufficient to reduce alcohol consumption. The purpose of this study was to investigate the course of alcohol consumption patterns following a citation for an alcohol policy violation. Participants were college students (N = 445) who received a citation for a campus alcohol policy violation at a small northeastern liberal arts college. Participants completed a Timeline Follow-Back (TLFB) indicating their daily alcohol use 2 weeks prior to the citation through 2 weeks after the citation. Results indicated that participants decreased their alcohol use following a citation event. However, the reduction in alcohol consumption was modest, suggesting that the citation event itself has a very temporary influence on the drinking of college students. Additional research is needed to reconcile these findings with those from other studies that found a more meaningful citation effect.